Geotechnical Characterization of Soils for Road Construction Along Textile Mill Road, Benin City, Nigeria - David Idiata; Ngozi Kayode-Ojo; Solomon Okonofua (ENP Engineering Science Journal, 2025)
This paper presents a geotechnical characterization of soil samples to evaluate their suitability for road construction. Laboratory tests, including specific gravity, sieve analysis, compaction, Atterberg limits, and California Bearing Ratio (CBR), were conducted to assess engineering properties. The results highlight significant variations in particle density, gradation, plasticity, and load-bearing capacity, which critically influence subgrade stability and pavement performance. The findings demonstrate that soils with higher specific gravity and well-graded particle distribution exhibit superior compaction characteristics and reduced moisture susceptibility. Lower plasticity indices correlate with enhanced stability under wet-dry cycles, minimizing long-term maintenance needs. CBR tests further reveal that soils with minimal strength loss under soaked conditions are more resilient, ensuring durability in moistureprone environments. The study underscores the importance of selecting soils with optimal gradation, density, and plasticity to achieve cost-effective and sustainable road infrastructure. Practical implications for construction practices, including moisture control and stabilization requirements, are discussed, providing actionable insights for engineers and project planners.